Out lander - Gabaldon, Diana (New York : A Dell Book, 2005)
Hurtled back through time more than two hundred years to Scotland in 1743, Claire Randall finds herself caught in the midst of an unfamiliar world torn apart by violence, pestilence, and revolution and haunted by her growing feelings for James Fraser, a young soldier.
Keywords: Time travel -- Fiction; Scotland -- Fiction. -- History -- 18th century